Traslación as a Digital Imagined Community: Discoursing the Interface Between Religion and Social Media - Urquiola, Luciana L. (The PASCHR journal, 2020)
This study problematizes the interface between religion and social media in the observance of Traslación. It uses Hegel’s dialectics of the progression of the three suppositions: thesis, anti-thesis, and synthesis, makes sense of this intersection in such a way that the synergy juxtaposes religion (thesis) and social media (anti- thesis) which when combined resolved their divergence resulting to digital religion (synthesis). Utilising Anderson’s Theory of Imagined Community, the study establishes the similar attributes between a political community and Traslación. However, the concept of Third Space by Bhaba and Media Arts Theory by Packer crystallize the postulations that Traslación which has both physical and online/digital dimensions can merge and become one as a digital imagined community.